Impact of Family Ownership on Market Value of a Firm: A Comparative Analysis of Family and Non-Family Companies Listed at Karachi Stock Exchange (Pakistan) - Tahir, Safdar Husain; Sabir, Hazoor Muhammad (International Journal of Management and Sustainability, 2015)
The current study attempts to investigate the impact of family ownership structure on value of firms listed at the Karachi Stock Exchange (KSE) of Pakistan. For the distinction of FOB from Non-FOB, two threshold points (25% & 50%) of ownership structure are used. A sample of 280 listed firms at KSE is collected ranging for the period 2002-13. Generalized Method of Moments (GMM) is applied on panel data to estimate the coefficients of variables. The empirical results indicate that the family firms outperform the non-family ones. The better performance of young generation of family firms over succeeding generation is also revealed but professional chief executive officer (CEO) over family member is preferred. Furthermore, this study discovers inflection points i.e. (62% & 57%) for family and non-family firms under quadratic specification respectively.